(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background:Badminton is a popular worldwide sport that requires fast and powerful shots and agile footwork. It is one of the fastest racket sports in the world. [1]The agility and vertical jump are important motor skills to hit a shuttlecock at different positions around the court. Objectives: To see the effect of plyometric training on jumping performance and agilityin badminton players.Methodology: 30 participants, both male and female were included in this study. All participants were tested for agility and vertical jump before and after 6-weeks plyometric training period. Agility performance was assessed using Agility T-Test and vertical jump height was assessed using vertical jump test. The participants performed plyometric training thrice a week, for 6 weeks.Results:The data was collected and statistically analysed using paired t test.The study concluded that there was an increase in vertical jump height(40.37±7.690cm) and agility (11.74±1.366sec) post plyometric training with significant p value (<0.0001).Conclusion:Our results show that six weeks plyometric training improved jumping performance and agility in badminton players.